Staphylococcus aureus populations from the gut and the blood are not distinguished by virulence traits—a critical role of host barrier integrity - Elisa J. M. Raineri; Sandra Maaß; Min Wang; Siobhan Brushett; Laura M. Palma Medina; Neus Sampol Escandell; Dania Altulea; Erwin Raangs; Anne de Jong; Elias Vera Murguia; Edward J. Feil; Alex W. Friedrich; et al. (Microbiome, 2022)
Abstract Background The opportunistic pathogen Staphylococcus aureus is an asymptomatically carried member of the microbiome of about one third of the human population at any given point in time. Body sites known to harbor S. aureus are the skin, nasopharynx, and gut. In particular, the mechanisms allowing S. aureus to pass the gut epithelial barrier and to invade the bloodstream were so far poorly understood. Therefore, the objective of our present study was to investigate the extent to which genetic differences between enteric S. aureus isolates and isolates that caused serious bloodstream infections contribute to the likelihood of invasive disease. Results Here, we present genome-wide association studies (GWAS) that compare the genome sequences of 69 S. aureus isolates from enteric carriage by healthy volunteers and 95 isolates from bloodstream infections. We complement our GWAS results with a detailed characterization of the cellular and extracellular proteomes of the representative gut and bloodstream isolates, and by assaying the virulence of these isolates with infection models based on human gut epithelial cells, human blood cells, and a small animal infection model. Intriguingly, our results show that enteric and bloodstream isolates with the same sequence type (ST1 or ST5) are very similar to each other at the genomic and proteomic levels. Nonetheless, bloodstream isolates are not necessarily associated with an invasive profile. Furthermore, we show that the main decisive factor preventing infection of gut epithelial cells in vitro is the presence of a tight barrier. Conclusions Our data show that virulence is a highly variable trait, even within a single clone. Importantly, however, there is no evidence that blood stream isolates possess a higher virulence potential than those from the enteric carriage. In fact, some gut isolates from healthy carriers were more virulent than bloodstream isolates. Based on our present observations, we propose that the integrity of the gut epithelial layer, rather than the pathogenic potential of the investigated enteric S. aureus isolates, determines whether staphylococci from the gut microbiome will become invasive pathogens. Video Abstract